Point-of-Care Diagnostic Device for Traumatic Pneumothorax: Low Sensitivity of the Unblinded PneumoScan™ - M. Rehfeldt; A. Slagman; B. A. Leidel; M. Möckel; T. Lindner (Emergency Medicine International)
Background. Traumatic Pneumothorax (PTX) is a potentially life-threatening injury. It requires a fast and accurate diagnosis and treatment, but diagnostic tools are limited. A new point-of-care device (PneumoScan) based on micropower impulse radar (MIR) promises to diagnose a PTX within seconds. In this study, we compare standard diagnostics with PneumoScan during shock-trauma-room management. Patients and Methods. Patients with blunt or penetrating chest trauma were consecutively included in the study. All patients were examined including clinical examination with auscultation (CE) and supine chest radiography (CXR). In addition, PneumoScan-readings and thoracic ultrasound scan (US) were performed. Computed tomography (CT) served as gold standard. Results. CT scan revealed PTX in 11 patients. PneumoScan detected two PTX correctly but missed nine. 15 false-positive results were found by PneumoScan, leading to a sensitivity of 20% and specificity of 80%. Six PTX were detected through CE (sensitivity: 54,5%). CXR detected four (sensitivity: 27,3%) and thoracic US two PTX correctly (sensitivity: 25%). Conclusion. The unblinded PneumoScan prototype did not confirm the promising results of previous studies. The examined standard diagnostics and thoracic US showed rather weak sensitivity as well. Until now, there is no appropriate point-of-care tool to rule out PTX.